Swinging Pendulum of History: Politics, Pedagogy and Unconsolidated Memory - Cooley, Rebecca I. (Tufts Archival Research Center, 2016)
The 1979 Sandinista Revolution ended four decades of dictatorial rule in Nicaragua. While political violence largely subsided, the ideological contestation continued via social memory in following four decades. As each new regime came to power, by revolutionary or democratic means, the incoming government sought to delegitimize, destroy and displaced the previous administration narrative of the recent national history. This thesis analyses this phenomenon through a constructivist lens and consider the consequences of this memory battle. Through the analysis of educational materials and interviews with current university students in Managua, this study delves into the complexities of memorializing recent history.